2021
DOI: 10.3390/ma14051196
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Refinement of a Transformation-Induced Plasticity High-Entropy Alloy

Abstract: High-entropy alloys (HEAs) have attracted extensive interest due to their unprecedented structure and mechanical performance. We recently proposed a series of novel corich twinning induced plasticity (TWIP) and transformation induced plasticity (TRIP) HEAs with superior tensile properties at room temperature; however, the hot deformation behavior has not been reported. Here, we investigated the dynamic recrystallization behavior and grain refinement of a representative TRIP-HEA, compressed at temperatures of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The volume fraction of the fine grains was 58%, and the volume fraction of the coarse grains was 42%, analyzed using the EBSD method described in a previous study [27]. Fine grains were produced by discontinuous dynamic recrystallization during HR, and the recrystallization behavior during hot deformation was systematically investigated in our previous study [22]. One can refer to the study for more details on the hot deformation and recrystallization characteristics of HEAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume fraction of the fine grains was 58%, and the volume fraction of the coarse grains was 42%, analyzed using the EBSD method described in a previous study [27]. Fine grains were produced by discontinuous dynamic recrystallization during HR, and the recrystallization behavior during hot deformation was systematically investigated in our previous study [22]. One can refer to the study for more details on the hot deformation and recrystallization characteristics of HEAs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanical properties have only been reported for as-recrystallized Co-rich HEAs. The microstructure has a strong correlation with the mechanical properties of metals and alloys, which are usually tuned by thermomechanical processing (TMP), such as rolling, compression, and torsion, combined with heat-treatment [20][21][22][23][24][25][26][27][28][29]. The influence of TMP on the resultant microstructure and the correlation between the microstructure and mechanical performance of the newly developed Co-rich HEAs have not yet been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent activation energy of the Cantor HEA is close to that of the diffusion of Ni in the alloy, and the dislocation climb determines the steady-state deformation [25][26][27][28][29][30][31][32]. Even though the DRX behaviors of CoCrNi MEA and the novel Co-rich TRIP HEA were investigated in our previous studies [14,24], the influence of interstitial atoms such as C and N on hot-deformation and grain structure evolution have not been clarified.…”
Section: Introductionmentioning
confidence: 94%
“…Deep insight into the hot-deformation mechanism, the microstructure evolution, and the DRX mechanism is a prerequisite for optimizing grain structures [20][21][22][23]. It was reported that discontinuous dynamic recrystallization (dDRX) notably contributed to grain refinement during hot-deformation, in which the recrystallized grains tend to nucleate at the primary grain boundaries (GBs) [14,24]. The apparent activation energy of the Cantor HEA is close to that of the diffusion of Ni in the alloy, and the dislocation climb determines the steady-state deformation [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed that highly concentrated alloys have superior properties in numerous applications compared to some conventional alloys [ 14 ]. As a result, HEAs attracted extensive scientific and industrial communities’ attention [ 15 , 16 , 17 ]. These alloys open new paths and applications due to their properties such as: good structural stability, high wear resistance, enhanced corrosion resistance, excellent thermal stability and high hardness [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%